2012
DOI: 10.1111/exd.12062
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian target of rapamycin complex 1 (mTORC1) may modulate the timing of anagen entry in mouse hair follicles

Abstract: inducing fast recruitment of MiTF into the nucleus, to activate transcription of enzymes and proteins related to melanogenesis and, at the same time, prevent MiTF degradation by lowering the level of P-ERK. Thus, the ability of IB-MECA to elevate DOPA oxidase activity, melanin synthesis and cell dendricity is in line with MiTF role in regulating melanin synthesis, melanosome transport and dendricity (23).In skin explants, IB-MECA induced an increase in melanization, when applied topically. Histological data sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
2

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 28 publications
1
24
2
Order By: Relevance
“…It was previously reported that mTOR may be required for HFSC activation and anagen entry (Castilho et al, 2009;Kellenberger and Tauchi, 2013;Deng et al, 2015). However, our results above indicate that moderate inhibition of mTOR by rapamycin accompanied by autophagy induction stimulates hair regeneration.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…It was previously reported that mTOR may be required for HFSC activation and anagen entry (Castilho et al, 2009;Kellenberger and Tauchi, 2013;Deng et al, 2015). However, our results above indicate that moderate inhibition of mTOR by rapamycin accompanied by autophagy induction stimulates hair regeneration.…”
Section: Resultscontrasting
confidence: 54%
“…Skin remains in telogen during this whole treatment period as confirmed by the lack of skin pigmentation. Number ”M does not enhance hair regeneration (data not shown); this may be due to more severe inhibition of mTOR which was reported to be required for HFSC activation (Castilho et al, 2009;Kellenberger and Tauchi, 2013;Deng et al, 2015). Number of animals: control (15), rapamycin (12).…”
Section: Figure Legendsmentioning
confidence: 94%
“…It has also been demonstrated that dendritic cell migration into the draining lymph node can be influenced by rapamycin . Mammalian target of rapamycin complex 1 (mTORC1) was also reported to modulate the timing of antigen entry in mouse hair follicles . Recently, several reports have suggested the therapeutic efficacy of rapamycin for various immunological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Skin thickness and size were evaluated by digital image analysis using Photoshop Âź software, and at least 50 longitudinally cut follicles per sample were counted. Then, the hair stage percentage and the HCS were classified and assessed by histomorphometry according to the previously published hair cycle staging guidelines and morphological characteristics of the murine hair cycle . For the anagen–catagen transition study, anagen VI HFs were assigned a score of 100, HFs in early catagen (catagen II–III) received a score of 200, while HFs in mid‐ and late catagen (catagen IV–V) were assigned a score of 300.…”
Section: Methodsmentioning
confidence: 99%